Survei Permasalahan Guru BK Pascapandemi - Mussilaturrohmi Mussilaturrohmi; Novita Tri Hapsari; Ana Susanti; Ma'rifatin Indah Kholili (Jurnal Psikoedukasi dan Konseling, 2022)
The objectives of this study are (1) to identify the conditions for implementing BK in schools and (2) to identify problems faced by counselors after the Covid-19 Pandemic. The research method uses surveys. Data collection techniques used questionnaires about counselors' problems after the Pandemic. The study population was counselors in Indonesia, and the research sample was 323 respondents from the islands of Java, Sumatra, Kalimantan, Sulawesi, Bali-NTT-NTB, and Maluku. Data analysis using descriptive statistics. The results of the study found that there were several obstacles experienced by counselor in the implementation of counselor services after the Pandemic, such as the imbalance in the ratio of counselors to students, the absence of class hours, the absence of instruments for counselors, and changes in the curriculum that caused changes in the design of the counselor program. These problems can be solved through cooperation from various parties. Support from schools, stakeholders and parents is needed so that the implementation of counselor services can be as planned. Suggestions for further research can be done by conducting literature reviews or conducting experimental research related to problems that occur after the pandemic.